(untitled) (Research, Society and Development, 2021)
Objective: To evaluate the importance of procalcitonin associated with cases of covid-19. Methodology: This is a literary review with qualitative construction, based on articles researched in the database of SciELO - Scientific Electronic Library Online, National Library of Medicine - PubMed and Virtual Health Library - VHL. Having as filter scientific articles published between the years 2016 to 2020, where the inclusion criteria will be: date of publication, freely available texts, among the articles previously selected, their abstracts will be read, and those that are not within the expected results will be excluded. The following descriptors will be used: covid-19, procalcitonin and biomarkers. Final considerations: The performance of this study demonstrates that the dosage of procalcitonin helps to distinguish critically ill and moderate severe patients. Studies have shown the evolution of the parameter in the laboratory sector regarding its use as an elementary tool in the covid-19 sector, in order to early identify patients with a presentable risk of bacterial co-infection and adverse effects, stratifying them according to the clinical and laboratory conditions, therefore, this foresight enables dexterity in therapeutic treatment, guiding the use of antibiotics, improving the prognosis.